Chemical Reduction Behavior of Zirconia Doped to Nickel at Different Temperature in Carbon Monoxide Atmosphere - Norliza Dzakaria; Maratun Najiha Abu Tahari; Fairous Salleh; Alinda Samsuri; Masitah Abdul Halim Azizi; Tengku Shafazila Tengku Saharuddin; Muhammad Rahimi Yusop; Wan Nor Roslam Wan Isahak; Mohamed Wahab Mohamed Hisham; Mohd Ambar Yarmo (Universitas Gadjah Mada, 2020)
The reduction behavior of nickel oxide (NiO) and zirconia (Zr) doped NiO (Zr/NiO) was investigated using temperature programmed reduction (TPR) using carbon monoxide (CO) as a reductant and then characterized using X-ray diffraction (XRD), nitrogen absorption isotherm using BET technique and FESEM-EDX. The reduction characteristics of NiO to Ni were examined up to temperature 700 °C and continued with isothermal reduction by 40 vol. % CO in nitrogen. The studies show that the TPR profile of doped NiO slightly shifts to a higher temperature as compared to the undoped NiO which begins at 387 °C and maximum at 461 °C. The interaction between ZrO2 with Ni leads to this slightly increase by 21 to 56 °C of the reduction temperature. Analysis using XRD confirmed, the increasing percentage of Zr from 5 to 15% speed up the reducibility of NiO to Ni at temperature 550 °C. At this temperature, undoped NiO and 5% Zr/NiO still show some crystallinity present of NiO, but 15% Zr/NiO shows no NiO in crystalline form. Based on the results of physical properties, the surface area for 5% Zr/NiO and 15% Zr/NiO was slightly increased from 6.6 to 16.7 m2/g compared to undoped NiO and for FESEM-EDX, the particles size also increased after doped with Zr on to NiO where 5% Zr/NiO particles were 110 ± 5 nm and 15% Zr/NiO 140 ± 2 nm. This confirmed that the addition of Zr to NiO has a remarkable chemical effect on complete reduction NiO to Ni at low reduction temperature (550 °C). This might be due to the formation of intermetallic between Zr/NiO which have new chemical and physical properties.